Health Literacy and Health Behavior Among Women in Ghazni, Afghanistan - Harsch, Stefanie; Jawid, Asadullah; Jawid, Ebrahim; Saboga-Nunes, Luis; Sørensen, Kristine; Sahrai, Diana; Bittlingmayer, Uwe H. (Frontiers in Public Health, 2021)
Background: Health literacy is a determinant of health and assessed globally to inform the development of health interventions. However, little is known about health literacy in countries with one of the poorest health indicators worldwide, such as Afghanistan. Studies worldwide demonstrate that women play a key role in developing health literacy. Hence, this study's purpose is to explore health literacy of women in Afghanistan and the associated factors. Methods: From May to June 2017, we randomly recruited 7–10 women per day at the hospital in Ghazni, a representative province of Afghanistan. Two trained female interviewers interviewed 322 women (15–61 years old) orally in Dari or Pashto on a voluntary basis and assessed their health literacy using the HLS-EU-Q16, associated socio-demographics, and health behavior. Results: Health literacy of women (among educated and illiterates) is low even compared to other Asian countries. Health literacy is linked to age and education. We found mixed evidence of the relationship between health literacy and contextual factors, help-seeking, and health-related behavior. Conclusion: This study provides novel data on health literacy and astonishing insights into its association with health behavior of women in Afghanistan, thus contributing to health status. The study calls for recognition of health literacy as a public health challenge be addressed in Afghanistan and other low-income countries affected by crises.